2021
DOI: 10.3390/cancers13061328
|View full text |Cite
|
Sign up to set email alerts
|

Future Prospects of Colorectal Cancer Screening: Characterizing Interval Cancers

Abstract: Tumors that are not detected by screening tests are known as interval cancers and are diagnosed clinically after a negative result in the screening episode but before the next screening invitation. Clinical characteristics associated with interval colorectal cancers have been studied, but few molecular data are available that describe interval colorectal cancers. A better understanding of the clinical and biological characteristics associated with interval colorectal cancer may provide new insights into how to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 99 publications
0
8
0
6
Order By: Relevance
“…There are two recent reviews that compare screen-detected versus FOBT interval cancer [ 9 , 24 ]. First, Wieten et al [ 24 ] published a systematic review and meta-analysis to evaluate the incidence rates of interval CRC following gFOBT and FIT in population-based CRC screening programmes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are two recent reviews that compare screen-detected versus FOBT interval cancer [ 9 , 24 ]. First, Wieten et al [ 24 ] published a systematic review and meta-analysis to evaluate the incidence rates of interval CRC following gFOBT and FIT in population-based CRC screening programmes.…”
Section: Discussionmentioning
confidence: 99%
“…They reported a lower incidence rate of interval cancer after a negative FIT than after the gFOBT (20 vs 34 interval CRCs per 100,000 person-years, respectively). Afterwards, our group performed a review [ 9 ] focused only in FIT-based population screening and found that the interval CRC proportion was around 15% and that interval cancers were more frequent in women and in the right colon and were staged more advanced. In this study, the findings are consistent with the literature as the interval cancer proportion was 45.3% for gFOBT and 17.7% for FIT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Program invitations are distributed according to geographical areas, but these differences have been minimized by adjusting for an aggregated deprivation index. Finally, the number of CRCs cases was relatively small, although we included a large number of subjects, and the proportion of interval cancer was consistent with previous literature [ 32 ].…”
Section: Discussionmentioning
confidence: 84%
“…CRC is among the cancers with tremendous somatic mutations causing high heterogeneity ( 8 , 9 ). In 15% of CRCs, the high mutational burden (>12 mutations per megabase) is due to a defect in the genes of mismatch repair (MMR) systems such as MLH1, MSH2, MSH6, and PMS2, which causes transcriptional problems, especially in regions with repetitive nucleotides such as microsatellites.…”
Section: Introductionmentioning
confidence: 99%